Maastik kui mänguväljak - Hannes Palang (Mäetagused, 2022)
This paper studies further the idea expressed by Paul Claval about landscape as a playground. For a decade, scholars have wondered whether games such as geocaching could be used if not in planning, then at least in getting feedback about people’s landscape preferences. This paper studies the role of geocaching in landscape changes through three lenses: geocaching as consumption of nature’s contribution to people, as influence on the environment, and as place making. The author concludes that, first, landscape can indeed serve as a playground and let the players inscribe on its layers of meaning understandable only for the dedicated (initiated). Second, the hope for getting feedback about preferences will probably fail, as the players care more about the contents of the game, but at the same time we could get insights into the preferences of the player communities. Finally, the game allows for recreating and remembering places and telling stories.